2021
DOI: 10.3390/toxins13050355
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Environmental Consequences of Bacillus thuringiensis Application for Natural Ecosystems

Abstract: Bacillus thuringiensis (Bt), a natural pathogen of different invertebrates, primarily insects, is widely used as a biological control agent. While Bt-based preparations are claimed to be safe for non-target organisms due to the immense host specificity of the bacterium, the growing evidence witnesses the distant consequences of their application for natural communities. For instance, upon introduction to soil habitats, Bt strains can affect indigenous microorganisms, such as bacteria and fungi, and further est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 204 publications
(263 reference statements)
0
30
0
1
Order By: Relevance
“…Some reviews summarize the potential of isolated Xn or Bt in the biological control of vectors and insect species harmful to agriculture [ 18 , 44 , 45 , 46 , 47 ]. However, the efficacy of these pathogens, when used in single, does not always provide satisfactory results; in addition, their efficacy often requires high concentrations of the pathogen, which can interfere with the life cycle and affect other beneficial organisms present in the environment [ 48 , 49 ]. The reduction of the administered concentrations and the improvement of the rapidity of action, could be achieved by combining different bioinsecticides, thus by exploiting the possible synergistic or additive potential of the applied pathogens [ 9 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reviews summarize the potential of isolated Xn or Bt in the biological control of vectors and insect species harmful to agriculture [ 18 , 44 , 45 , 46 , 47 ]. However, the efficacy of these pathogens, when used in single, does not always provide satisfactory results; in addition, their efficacy often requires high concentrations of the pathogen, which can interfere with the life cycle and affect other beneficial organisms present in the environment [ 48 , 49 ]. The reduction of the administered concentrations and the improvement of the rapidity of action, could be achieved by combining different bioinsecticides, thus by exploiting the possible synergistic or additive potential of the applied pathogens [ 9 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Bt Cry3 proteins are highly specific for Coleoptera and exert their toxic action once ingested by susceptible insects through a number of sequential steps encompassing crystal solubilization and subsequent protoxin release, followed by toxin activation by midgut proteases, and binding of the activated toxin to midgut specific receptors that promote toxin oligomerization and formation of pores in the midgut epithelial cells, eventually leading to cell death. 6 We have previously demonstrated that interaction of Cry3Aa protein with an ADAM10 metalloprotease in the midgut membrane is key in the mechanism of action of this toxin in CPB larvae. 7 The potential for CPB to evolve resistance to Cry3Aa toxin has been evidenced by the results of selection experiments in the laboratory following repeated Cry3A toxin applications, and changes in digestive enzyme profiles as well as lower toxin binding have been proposed as adaptive responses that render larvae resistant to Cry3Aa toxin.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Cry3Aa toxin, deployed in foliar sprays as well as in genetically modified potato plants, has been proved to display effective insecticidal activity against CPB 5 . Bt Cry3 proteins are highly specific for Coleoptera and exert their toxic action once ingested by susceptible insects through a number of sequential steps encompassing crystal solubilization and subsequent protoxin release, followed by toxin activation by midgut proteases, and binding of the activated toxin to midgut specific receptors that promote toxin oligomerization and formation of pores in the midgut epithelial cells, eventually leading to cell death 6 . We have previously demonstrated that interaction of Cry3Aa protein with an ADAM10 metalloprotease in the midgut membrane is key in the mechanism of action of this toxin in CPB larvae 7 …”
Section: Introductionmentioning
confidence: 99%
“…The ecological safety of transgenic crops has been a focus of scientific research and public debate [ 1 , 2 , 3 ]. Specifically, the effects of transgenic crops with Bacillus thuringiensis (Bt) gene on non-target organisms are of great concern in ecological risk assessment [ 4 ]. Bt cotton can significantly reduce damage by insect pests [ 5 ]; however, Bt toxin expression and insect resistance in transgenic cotton vary in different organs or tissues during different growth periods [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%